The implementation of e-learning with team builder at vocational high schools - Patwary, Mahmud Al Haq; Surjono, Herman Dwi (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2015)
This research is aimed at: (1) producing an appropriate e-learning for English language studies in vocational high school, (2) evaluating the suitability of the developed e-learning in terms of appropriateness, accuracy and clarity, screen presentation and design, and appropriateness of the team builder module aspect, and (3) evaluating the effectiveness of the e-learning in practical application. This research and development (R&D) study used Alessi and Trollip's model rearranged following ADDIE model, where the development of instruction followed Dick and Carey's model and the need assessment procedures were adapted from Lee & Owens. Overall appropriateness and quality of the e-learning from alpha testing is